2017
DOI: 10.1039/c7ob00295e
|View full text |Cite
|
Sign up to set email alerts
|

2,2,2-Trifluoroethanol as a solvent to control nucleophilic peptide arylation

Abstract: The SAr arylation of peptides with perfluoroaromatics provides a route by which to install a useful chemical handle that enables both F-NMR analysis and further chemical modification. However, chemo-selective arylation in peptides containing multiple nucleophilic side chains currently presents a challenge to the field. Herein, we demonstrate that employing 2,2,2-trifluoroethanol (TFE) as a solvent in peptide SAr reactions significantly improves nucleophile-selectivity when compared to N,N'-dimethylformamide (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…In addition, our own group has reported the use of PFP as a tagging reagent in peptide chemistry. We observed that PFP could undergo S N Ar reactions with peptides containing nucleophilic side-chains, including tyrosine 15. We have also developed a range of unnatural amino acids using the same chemistry 16…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our own group has reported the use of PFP as a tagging reagent in peptide chemistry. We observed that PFP could undergo S N Ar reactions with peptides containing nucleophilic side-chains, including tyrosine 15. We have also developed a range of unnatural amino acids using the same chemistry 16…”
Section: Introductionmentioning
confidence: 99%
“…The role of the fluorinated solvent, TFE can be rationalized as follows. Kita and coworkers have shown that when hypervalent iodine reagents are mixed with fluorinated solvents like hexafluoroisopropanol (HFIP), radical‐cation intermediates are stabilized due to the high polarity and low nucleophilicity of the solvent.…”
Section: Resultsmentioning
confidence: 99%
“…Kita and coworkers have shown that when hypervalent iodine reagents are mixed with fluorinated solvents like hexafluoroisopropanol (HFIP), radical‐cation intermediates are stabilized due to the high polarity and low nucleophilicity of the solvent. [40d] Recently, Donohoe and Compton and coworkers also demonstrated the role of HFIP in the activation of the hypervalent iodine reagents . Similarly, trifluoroethanol is also known to be a fluorinated solvent that could stabilize cationic or radical‐cation species generated using iodine regents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their highly electron deficient nature, perfluoroaromatics can have significant effects on the electronics of molecular systems [ 60 ]. Perfluoroaromatic moieties have therefore seen use in materials [ 61 ], catalysis [ 62 , 63 ] and organic synthesis [ 64 , 65 ], and have been exploited in peptide [ 66 , 67 ] and peptoid chemistry [ 68 ]. Access to highly fluorinated amino acids is therefore an area of much research, with several reports detailing the synthesis of aromatic perfluorinated amino acids.…”
Section: Complex Fluorine-containing Aromatic Amino Acidsmentioning
confidence: 99%